Alternatives in Grammar and Cognition - Gotzner, Nicole; Harris, Jesse A.; Breheny, Richard; Sharvit, Yael (Palgrave Studies in Pragmatics, Language and Cognition, 2024)
XVII, 309 p. 155 illus., 8 illus. in color.